Generation of stretched pulses from an all-polarization-maintaining Er-doped mode-locked fiber laser using nonlinear polarization evolution. (24th April 2019) - Zhou, Lian; Liu, Yang; Xie, Gehui; Zhang, Wenchao; Zhu, Zhiwei; Ouyang, Cheng; Gu, Chenglin; Li, Wenxue
Abstract: We demonstrate the generation of stretched pulses from an all-polarization-maintaining (all-PM) Er-doped fiber laser by means of a nonlinear polarization evolution (NPE) method. A theoretical model is built to analyze the relationship between the nonlinear transmissivity and the angles of the fiber segments. By managing the dispersion of the oscillator to support stretched-pulse formation and exploiting an NPE section based on three PM fiber segments, a self-starting laser with a 90.5-MHz repetition rate and 90-fs pulse duration is achieved. Numerous laser systems can benefit from this approach, including frequency combs, outdoor ranging and mid-IR systems.